PENGARUH LINGKUNGAN SEKOLAH DAN LINGKUNGAN KELUARGA TERHADAP PEMBENTUKAN AKHLAK PESERTA DIDIK - Sutarno; Jaenullah; Anggraini, Dian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of school and family environments on students’ moral development. The research is motivated by variations in students’ moral behavior, including differences in discipline, responsibility, and social attitudes, which indicate the role of environmental factors. This study employed a quantitative approach with an associative design. The sample consisted of 60 eighth-grade students selected using cluster sampling. Data were collected through questionnaires supported by observation and documentation, and analyzed using multiple linear regression. The results show that the school environment has a significant effect on students’ moral development (sig. = 0.033 < 0.05), and the family environment also has a significant effect (sig. = 0.026 < 0.05). Simultaneously, both variables have a significant influence (F = 12.951; sig. = 0.000 < 0.05). The regression analysis indicates that the family environment has a more dominant influence compared to the school environment. The coefficient of determination shows that 31.2% of moral development is influenced by school and family environments, while the remaining is influenced by other factors.